Gender inequality. A multidimensional measurement proposal for Mexico - Zamora Torres, América Ivonne; Díaz Barajas, Yesica; Navarro Chávez, José César Lenin (Revista Punto Género, 2023)
This study aims to identify how reproductive health, empowerment, and labor influence gender inequality in the Mexican states in 2020, using a methodological approach based on the Gender Inequality Index (GII) presented by the United Nations Development Programme (UNDP) in 2014. It applies an expanded index that incorporate four complementary empowerment and labor indicators to the field of gender studies. This approach reveals Mexico’s main inequalities between women and men, and enables a comparison with the results of the original GII.The findings show that, in general, the extended model records greater inequality on average (11%). The deepened gender inequality gap requires the implementation of public policies to advance towards a greater equality in human development.